2022
DOI: 10.1186/s43163-022-00222-0
|View full text |Cite
|
Sign up to set email alerts
|

Common vestibular disorders in children in Fayoum governorate: a cross-sectional study

Abstract: Background Vertigo in paediatric age is not a rare condition. However, a lack of awareness about causes of dizziness in children besides the absence of standard diagnostic workup often leads to unnecessary procedures in managing these cases. The purpose of this cross-sectional study was to determine the prevalence and frequency distribution of balance abnormalities in dizzy children. Additionally, the questionnaire’s utility as a screening tool and its predictive accuracy are discussed. Thus, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…According to Elghaffar et al, 2022, the indicated diagnosis was that 17.6% of the patients had benign paroxysmal vertigo of childhood and 23.9% of the cases had dizziness associated with otitis media [10]. Patients with migraines made up 11.2%, while 5.5% of cases had benign paroxysmal positional vertigo, compared to 4.4%, who had labyrinthitis or vestibular neuritis.…”
mentioning
confidence: 99%
“…According to Elghaffar et al, 2022, the indicated diagnosis was that 17.6% of the patients had benign paroxysmal vertigo of childhood and 23.9% of the cases had dizziness associated with otitis media [10]. Patients with migraines made up 11.2%, while 5.5% of cases had benign paroxysmal positional vertigo, compared to 4.4%, who had labyrinthitis or vestibular neuritis.…”
mentioning
confidence: 99%